Evaluasi Usability Test e-Repository dengan menggunakan Metode Nielsen’s Attributtes of Usability (NAU) - Taufiq Iqbal; Bahruni Bahruni (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2019)
In meeting good software standards, testing of software quality is required. Usability is an aspect of software The purpose of this study is to obtain the usability test evaluation results on AMIK Indonesia's e-Repository with the efficiency and error factor based on the Nielsen's Attributes of Usability (NAU) questionnaire method, so that later it will be made as a suggestion and recommendation for the development of AMIK Indonesia's e-Repository based on the results The test is to improve the quality of the website in the usability aspect. This research method is divided into 4 stages consisting of activities in it, consisting of; 1) Initiation, 2) Pre-User Testing, 3) Pre-User Testing, and 4) Post User Testing. The sample of users was 22 students consisting of Class 2015, 2016, 2017 and 2018 who were active students of AMIK Indonesia. From the results of the achievement of research conducted that the usability test with Nielsen's Attributes of Usability (NAU) model can be applied in finding the quality level of a website. From the test results, the level of success in the UT-7, UT-8, and UT-10 tests with achievements of less than 80% of respondents failed to answer. For success rates above 80% on testing UT-1, UT-2, UT-3, UT-4, UT-5, UT-6, and UT-9. The results of the analysis carried out very satisfying interpretation of 14, Satisfied 1, Satisfied 2, Not Satisfied 1. As for the interpretation of dissatisfaction with questions with the ER14 code and quite satisfied with the ER12 and ER13 codes which are all three dimensions of error.